A STABILITY INDICATING UV SPECROPHOTOMETRIC METHOD FOR DETERMINATION OF METOCLOPRAMIDE HYRDROCHLORIDE - Deokate, U. A.; Gorde, Anjali Macchindra (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
A stability indicating method has been developed for specific determination of Metoclopramide HCl in bulk by UV spectrophotometry in presence of its degradation products. The method is simple, accurate, precise, and robust. Linearity range for the method is 10-50µg/ml at detection wavelength of 272 nm. The LOD and LOQ values were found to be 3.26µg/ml and 9.89µg/ml respectively.